Organizational Identity and Organizational Identification: A Review of the Literature and Suggestions for Future Research. (February 2013) - He, Hongwei; Brown, Andrew D.
In this article, we present an overview of the literatures on organizational identity and organizational identification. We provide overviews of four major approaches to organizational identity: functionalist, social constructionist, psychodynamic, and postmodern. The literature on organizational identification, by contrast, exhibits greater consensus due to the hegemonic power of social identity theory, and is predominantly functionalist. We review recent research on organizational identification regarding performance outcomes and antecedents (mainly focusing on leadership and the social exchange perspective), and in relation to change and virtual contexts. Some suggestions for further research are then offered. Finally an overview of the articles in this special issue is presented.